2021
DOI: 10.1142/s179354582140006x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of edema progression in permanent and transient MCAO model using SS-OCT

Abstract: Cerebral edema is a severe complication of acute ischemic stroke with high mortality but limited treatment. Although parameters such as brain water content and intracranial pressure may represent the global assessment of edema, optical properties can appear heterogeneously throughout the cerebral tissue relative to the site of injury. In this study, we have monitored the edema formation and progression in both permanent and transient middle cerebral artery occlusion models in rats. Edema was reflected by the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…This makes OAC a competent parameter to distinguish edema tissue from normal tissue. 45 , 90 We found that OAC value reduced uniformly throughout the brain, indicating a global edema condition, coincided with the vasogenic edema observed with MRI hyperintensities in ARIA. 12 , 92 …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This makes OAC a competent parameter to distinguish edema tissue from normal tissue. 45 , 90 We found that OAC value reduced uniformly throughout the brain, indicating a global edema condition, coincided with the vasogenic edema observed with MRI hyperintensities in ARIA. 12 , 92 …”
Section: Discussionsupporting
confidence: 62%
“… 89 We have also successfully utilized it to assess the water content and cerebral edema resulted from cerebral infarction. 45 , 90 In this study, the average OAC value of brain tissue decreased dramatically over time after ventricular injection of ( Fig. 8 ).…”
Section: Discussionsupporting
confidence: 53%
“…Optical coherence tomography (OCT), which reconstructs depth information images of biological tissues using backscattered light from the sample, has the advantages of non-contact, non-invasive and a high resolution [21]. OCT technology appeared in the 1990s and gradually transited to frequency domain OCT from time domain OCT [22].…”
Section: Introductionmentioning
confidence: 99%